Implementasi Kota Layak Anak Melalui Program Sekolah Ramah Anak (SRA) di Kota Bekasi - Sarah Fitriya Anandasari; Rahmat Hidayat; Mochamad Faizal Rizki (Jurnal Kajian Ilmiah, 2021)
High rates of abuse, whetever physcial, psycological or sexual, have come to the world’s attention because it violates the rights of the child which also brought human rights to got protection. With the introduction of the new order, we have no need such things as life itself. Where the school going to be a student expression space. The study used a qualitative approach with a type of descriptive research that described how to city’s child implemented process through a child-friendly school in Bekasi used three elements according to Ripley and Franklin. Policy result is realized the desired performance and impact.